Kondisi Sarana dan Prasarana Perpustakaan sebagai Fasilitas Gerakan Literasi di Sekolah Dasar - Amelia, Nisa; Apriliya, Seni; Alia, Dwi (CV. ITTC INDONESIA, 2024)
Based on international research, Indonesia is a country whose population is relatively low in terms of literacy. The latest test results conducted by PISA in 2022 also showed that the score obtained decreased by 12 points. Some experts say that the condition of library facilities and infrastructure is an external factor in low student interest in reading. The purpose of this study is to present the results of an analysis of the condition of library facilities and infrastructure as a facility for the literacy movement in elementary schools. The research method used was a qualitative approach. Data collection was conducted using observation and interview techniques with 3 librarians, 3 principals, 18 teachers and 90 students from 3 elementary schools in one of the cities in West Java. The analysis of the condition of library facilities and infrastructure carried out refers to the National Standards for SD / MI Libraries precisely according to the Regulation of the Head of the National Library of the Republic of Indonesia No. 10 of 2017. The results showed that SDN A has many aspects that have met the national standards, SDN B has quite a lot of aspects that have met the national standards, there are only a few shortcomings in both SDNs, and SDN C requires a lot of development in order to meet national standards. With library facilities and infrastructure that meet national standards, it is hoped that they can support the literacy movement.